Experiences of abuse in Australian family carers and predictors of mental health and well‐being. (28th August 2020) - Obst, Patricia; Murray, Kate; Walbank, Sarah; Kelly, Rachel; Brazel, Danielle
Abstract: Caregivers for family or friends who are elderly people or have a disability provide critical supports, with a range of positive and negative consequences associated with their role. This research explores the positive and negative aspects of care‐giving, including the experience of abuse within the caring relationship, through an anonymous online survey of the mental health, well‐being and caring experience of Australian family carers ( N  = 305). The voluntary participants were recruited through local and national carer associations. Over 40% of respondents reported having experienced abuse by the person they cared for, with the most common form of abuse being verbal abuse (35% of the respondents reporting abuse) and physical abuse (14%). The experience of abuse was related to poorer mental health as measured by the DASS‐21 and a lower reported quality of life. Financial stress, lack of support and the negative impacts of care‐giving were also significantly associated with mental health and well‐being outcomes. The current research is among the first to directly assess the experience of abuse within a broad sample of caregivers, identifying this as a significant issue for caregivers. The findings have clear implications for programs and policies that protect the rights, safety and well‐being of caregivers.